2021
DOI: 10.1002/adhm.202100994
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Confined Effects of Nanostructures on Fibronectin‐Induced Macrophage Inflammation on Titanium Implants

Abstract: Macrophage activation determines the fate of biomaterials implantation. Though researches have shown that fibronectin (FN) is highly involved in integrin-induced macrophage activation on biomaterials, the mechanism of how nanosized structure affects macrophage behavior is still unknown. Here, titanium dioxide nanotube structures with different sizes are fabricated to investigate the effects of nanostructure on macrophage activation. Compared with larger sized nanotubes and smooth surface, 30 nm nanotubes exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…So far, TiO 2 NTAs have been suggested to affect protein adsorption, cell behaviors like adhesion, proliferation and differentiation through the recognition between cell and implant surface. 23 , 40–42 In detail, the TiO 2 NTAs impact the osteointegration via protein adsorption, 52 platelet activation, 42 inflammatory response 16 and osteogenic property. 53 Hence, in this review, the biological role of TiO 2 NTAs at each stage in osseointegration will be discussed.…”
Section: Tio 2 Nano-topographymentioning
confidence: 99%
See 3 more Smart Citations
“…So far, TiO 2 NTAs have been suggested to affect protein adsorption, cell behaviors like adhesion, proliferation and differentiation through the recognition between cell and implant surface. 23 , 40–42 In detail, the TiO 2 NTAs impact the osteointegration via protein adsorption, 52 platelet activation, 42 inflammatory response 16 and osteogenic property. 53 Hence, in this review, the biological role of TiO 2 NTAs at each stage in osseointegration will be discussed.…”
Section: Tio 2 Nano-topographymentioning
confidence: 99%
“…For instance, it is demonstrated that TiO 2 NTAs of 30 nm diameter show noticeably weakened pro-inflammatory properties on macrophage polarization, since the adsorbed fibronectin, which is reported to be involved in the manipulation of integrin-induced macrophage behavior on biomaterial, displayed different conformations as the nanotube size changed, specific in the changing of exposed Arg-Gly-Asp (RGD) domain. 52 , 81 TiO 2 NTAs of 30 nm diameter allow the maximum exposure of RGD domain in fibronectin. 52 Hence, TiO 2 NTAs can regulate the protein conformation, which is also significant in protein adsorption, even more critical than the adsorbed concentration.…”
Section: The Impact Of Tio 2 Ntas On Titanium Impl...mentioning
confidence: 99%
See 2 more Smart Citations
“…A significant increase in the expression of fibronectin for the Li_Ti surface was also observed. Elevated fibronectin levels as an indicator of effective adhesion are well-established in the literature [54][55][56][57]. Indeed, it is the one glycoprotein produced by fibroblasts that regulates the adhesion process [58], acting as a "glue" for cell attachment.…”
Section: Gingival Fibroblasts Response To the Surfacementioning
confidence: 99%